OTHERNESS REPRESENTED IN TODD DURHAM’S HOTEL TRANSYLVANIA - Nasrum, Nasrum; Junaid, Syahruni; Awwab, Ashril (Laboratorium Informasi & Publikasi Fakultas Humaniora UIN Maulana Malik Ibrahim Malang, 2021)
This research discusses the otherness concept in Hotel Transylvania film. It is an animation movie that tells about the conflict between human with monster, in which the main character Dracula as a monster had a terrible memory with the human that makes him isolated himself and all monsters from humans’ intervention. The research aims to deconstruct how the otherness concept appeared in the film's manuscript. This research uses the content analysis method. In analyzing the data, the researchers use the deconstruction theory from Jacques Derrida to reveal the concept of otherness, which is the primary purpose of this research. Furthermore, this research focuses on the characters who brought the concept of otherness through their dialogue. As a result of this research, the researchers find that both humans and monsters are projecting each other's identity based on their perspective. The implication of this research is to give understanding to readers how the otherness concept is close to our daily life, and even we do not realize it has frequently happened.